2002
DOI: 10.1177/082585970201800203
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Safety and Clinical Effectiveness of Controlled-Release Metoclopramide in Cancer-Associated Dyspepsia Syndrome: A Multicentre Evaluation

Abstract: Patients with cancer frequently report gastrointestinal symptoms such as anorexia, early satiety, nausea, vomiting, and bloating. A reduction of the severity of some of these symptoms would benefit the patient by enhancing quality of life and improving their treatment. Forty-eight patients (25 female and 23 male; mean age 63 ±11 years) with a minimum two-week history of cancer-associated gastrointestinal symptoms were assigned to a single, open-label treatment group and received controlled-release metocloprami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…There was a statistically significant improvement in nausea in three studies and of vomiting in two series, but the studies vary in quality and methodology, and the numbers of patients included is small. Subsequently, a further uncontrolled study of controlled-release metoclopramide has been published suggesting benefit in the control of cancerassociated dyspepsia syndrome [18]. A recent systematic review of the efficacy of antiemetics in the treatment of nausea in patients with far-advanced cancer confirms the lack of evidence to support existing consensus-based guidelines for the management of N/V and points to the need for more well-designed studies [19].…”
Section: Discussionmentioning
confidence: 96%
“…There was a statistically significant improvement in nausea in three studies and of vomiting in two series, but the studies vary in quality and methodology, and the numbers of patients included is small. Subsequently, a further uncontrolled study of controlled-release metoclopramide has been published suggesting benefit in the control of cancerassociated dyspepsia syndrome [18]. A recent systematic review of the efficacy of antiemetics in the treatment of nausea in patients with far-advanced cancer confirms the lack of evidence to support existing consensus-based guidelines for the management of N/V and points to the need for more well-designed studies [19].…”
Section: Discussionmentioning
confidence: 96%
“…Whereas the uncontrolled studies had high response rates (75-93%) to standard regimens, the RCT had much lower responses rates (23-36% for nausea, 18-52% for vomiting). Similar response rates were achieved whether drug selection was empirical [18,19,21,27] or based on the patient's clinical picture [8,9,16,20].…”
Section: Quantitative Data Synthesismentioning
confidence: 92%
“…The initial Medline and EmBase searches for nausea and vomiting in advanced cancer produced a list of more than 1100 citations, of which only 22 (1.9%) had titles that appeared relevant to the topic of the review. Limiting the search to meta-analyses revealed seven citations, only one of which appeared relevant [16], the others all relating to chemotherapy-induced emesis. A systematic review of haloperidol, published as a letter and not coded electronically as a systematic review, was found subsequently when searching for uncontrolled studies [17].…”
Section: Trial Flowmentioning
confidence: 99%
See 2 more Smart Citations